Akuntabilitas dan transparansi pengelolaan keuangan desa pada Desa Komus Ii Timur Kabupaten Bolaang Mongondow Utara - Einar Einar; Hendrik Gamaliel; Peter M. Kapojos (Riset Akuntansi dan Portofolio Investasi, 2026)
Effective village financial management is fundamental to strengthening good governance at the local level. This study investigates the implementation of accountability and transparency in village financial management at Komus II Timur Village, North Bolaang Mongondow Regency, Indonesia. Employing a qualitative case study approach, data were collected through interviews, observations, and document analysis involving village officials, the Village Consultative Body, and community representatives. The findings reveal that accountability and transparency have been largely institutionalized across the planning, implementation, administration, reporting, and accountability stages, particularly through participatory decision-making, orderly financial administration, timely reporting, and public access to financial information. However, capacity constraints and uneven regulatory understanding among village officials remain notable challenges. The study underscores the importance of continuous capacity building and strengthened oversight mechanisms to enhance accountable and transparent village financial governance.